2010
DOI: 10.1007/s00134-010-2088-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoparalysis and nosocomial infection in children with multiple organ dysfunction syndrome

Abstract: Purpose Immunoparalysis defined by prolonged monocyte human leukocyte antigen DR depression is associated with adverse outcomes in adult severe sepsis and can be reversed with granulocyte macrophage colony-stimulating factor (GM-CSF). We hypothesized that immunoparalysis defined by whole-blood ex vivo lipopolysaccharide-induced tumor necrosis factor-alpha (TNFα) response <200 pg/mL beyond day 3 of multiple organ dysfunction syndrome (MODS) is similarly associated with nosocomial infection in children and can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
330
2
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(359 citation statements)
references
References 35 publications
8
330
2
7
Order By: Relevance
“…The hospital mortality rate of 25% confirms that severe sepsis remains a critical public 23 (12-28) 20 (5-26) 21 25 (19-28) 26 (20-28) 25 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 22 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) ,0.001…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The hospital mortality rate of 25% confirms that severe sepsis remains a critical public 23 (12-28) 20 (5-26) 21 25 (19-28) 26 (20-28) 25 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 22 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) ,0.001…”
Section: Discussionmentioning
confidence: 87%
“…Hospital mortality was 25% and did not differ by age or between developed and resourcelimited countries. Median ventilator-free days were 16 (IQR, 0-25), and vasoactive-free days were 23 (IQR,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Sixty-seven percent of patients had multiorgan dysfunction at sepsis recognition, with 30% subsequently developing new or progressive multiorgan dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regeneration of the monocyte function reduced in-hospital and ICU stay (24,25). In addition, several trials showed a lower susceptibility for nosocomial infections under GM-CSF therapy in paediatric patients (24,26). Beside IFN-γ and GM-CSF, IL-7 seems to be of potential value in (re)activation of the immune system.…”
Section: Immuno-stimulatory Strategiesmentioning
confidence: 99%
“…Children with septic shock may have immunoparalysis [111], and particular attention must be paid to ensuring that risks of nosocomial infection are decreased as far as possible [111]. It is particularly important in environments where many children have infections, and the number of available staff is limited to focus on the needs for reduction of patient-to-patient transmission of infection.…”
Section: Nosocomial Infectionmentioning
confidence: 99%